Enhancing the Precision and Efficiency of Pulmonary Tumor Detection With Robotic‐Assisted 18F‐FDG PET/CT‐Guided Lung Biopsy: A Case Report - Jian Liu; Chuan Xu; Haiyan Li; Bing Niu; Kai Xu; Xia Lu (Thoracic Cancer)
ABSTRACT Sarcomatoid carcinoma, a rare and aggressive form of non‐small cell lung cancer, presents diagnostic challenges due to its heterogeneity and atypical features. This case report evaluates robotic‐assisted 18F‐FDG PET/CT‐guided percutaneous lung biopsy for improving diagnostic accuracy and efficiency in such complex lung lesions. We present the case of an 86‐year‐old male with a right upper lung lesion, chronic cough, intermittent hemoptysis, chills, and fever. Initial fiberoptic bronchoscopy and CT‐guided lung biopsy (16 min, three needle adjustments) were inconclusive. Subsequently, a robotic‐assisted PET/CT‐guided percutaneous lung biopsy was performed, targeting metabolically active regions. This procedure was completed in 6 min without any needle adjustments. This efficiency stemmed from the system's clear, precise navigation, eliminating extensive manual lesion localization and collision risk with critical structures. Unlike some navigated procedures, it avoids time‐consuming marker placement and registration. Its high accuracy guidance facilitated single needle insertion, preventing repeated adjustments, confirmatory CTs, and step‐by‐step needle advancement. Imaging confirmed a hypermetabolic lesion and mediastinal lymphadenopathy suggestive of malignancy, and histopathology revealed sarcomatoid carcinoma with pleomorphic atypical cell infiltration, high mitotic activity, and necrosis. Genetic testing identified a MET mutation, leading to targeted therapy with Bozitinib. Follow‐up imaging at 1 month showed a significant reduction in the lesion size, indicating a positive treatment response. This case underscores the potential advantages of robotic‐assisted 18F‐FDG PET/CT‐guided lung biopsy in enhancing diagnostic sensitivity and procedural efficiency by precisely targeting metabolically active areas, minimizing needle adjustments, and potentially reducing false‐negative results. Broader application in interventional radiology and oncology warrants further investigation.